Full term premature rupture of the membrane (PROM): Active management (AM) vs conservative management (CM) - Sulchan Sofoewan Sulchan Sofoewan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The management of premature rupture of the membrane (PROM) is one of the most controversial areas in obstetrics. In the case of full term PROM, the obstetrician is often faced with either immediate induction of labor with higher incidence of caesarean section or awaiting spontaneous labor with higher incidence of chorioamnionitis.Objective: To compare pregnancy outcomes between active management (AM) and conservative management (CM) in full term PROM.Methods: The study was carried out in randomized controlled trial at the Department of Obstetrics and Gynecology, Faculty of Medicine, Gadjah Mada University/Sardjito Hospital Yogyakarta. Sixty full term PROM cases admitted to the hospital between July-December 1994 were randomly allocated into AM (n=30) and CM (n=30).Results: Caesarean section rate due to the failure of induction among AM group was significantly higher than those in CM group (p= 0.03). Maternal and perinatal infection were not statistically significant (p>0.50). The total number of newborn babies with asphyxia was higher in AM group but no statistical significant difference was found (p> 0.50).Conclusion: The conservative management of full term PROM was better compared to active management, especially when the outcome is caesarean section rate due to the failure of induction:Key words: PROM - active management - conservative management.